2015
DOI: 10.1098/rsbl.2015.0707
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetics of tragelaphine and alcelaphine interspecies hybrids: hybridization, introgression and speciation in some African antelope

Abstract: Hybridization can occur naturally among diverging lineages as part of the evolutionary process leading to complete reproductive isolation, or it can result from range shifts and habitat alteration through global warming and/or other anthropogenic influences. Here we report a molecular cytogenetic investigation of hybridization between taxonomically distinct species of the Alcelaphini (Alcelaphus buselaphus 2n = 40 × Damaliscus lunatus 2n = 36) and the Tragelaphini (Tragelaphus strepsiceros 2n = 31/32 × Tragela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Other reported cases of interspecific hybridization in bovids have shown that even if the parent species have different chromosome numbers, female offspring can be fertile, for example, in an Alcelaphus buselaphus × Damaliscus lunatus cross reported by Robinson et al. (2015). So maybe one fertile female hybrid was enough to keep the subgutturosa haplotype in the G. bennettii population.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other reported cases of interspecific hybridization in bovids have shown that even if the parent species have different chromosome numbers, female offspring can be fertile, for example, in an Alcelaphus buselaphus × Damaliscus lunatus cross reported by Robinson et al. (2015). So maybe one fertile female hybrid was enough to keep the subgutturosa haplotype in the G. bennettii population.…”
Section: Discussionmentioning
confidence: 96%
“…It is surprising therefore to find hybrids of the two species that seem to be fertile and interbreeding with pure G. bennettii in the wild. Interspecific hybrids in other bovid species (e.g., Alcelaphines, Tragelaphines) with (and without) different chromosome numbers were found to be infertile, at least in males (Robinson, Cernohorska, Schulze, & Duran‐Puig, 2015; Vaz Pinto et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa there has been considerable concern about introgression of southern blue wildebeest Connochaetes taurinus genes into the local endemic black wildebeest Connochaetes gnou following inopportune introductions of the former species into the latter's range (Grobler et al., ). But many more taxa seem affected; some cases have been discussed in detail, such as hybridizations between greater kudu and lowland nyala Strepsiceros strepsiceros × Tragelaphus angasi , or red hartebeest and tsessebe Alcelaphus buselaphus × Damaliscus lunatus (Robinson et al., ). Furthermore, admixtured populations of the Karoo and Kalahari springbok ( Antidorcas spp.)…”
Section: The Role Of Hybridization In Species Concepts and Conservationmentioning
confidence: 99%